Uma reavaliação do papel de Hípias de Élis como fonte protodoxográfica - Gustavo Laet Gomes (2023)
In 1944, Bruno Snell inaugurated a new field of research we may call Protodoxographical Studies by arguing that there should be a common source for parallel passages with doxographic features in Plato and Aristotle, which he identified as the sophist Hippias of Elis. Later scholars – in particular, Joachim Classen, Jaap Mansfeld, and Andreas Patzer – replicated his method for other parallel passages, and thereby expanded the range of possible content from Hippias. This generalization, however, has not come without methodological losses, in particular a gradual dismissal of parallel confirmatory anchors for the suggested passages: for Patzer, for example, the mere occurrence of parallel texts with a structure similar to the one originally identified by Snell would be taken as an unequivocal sign of the presence of Hippias. One of the effects of this precedent was the propagation of a hypertrophied image of Hippias as philosopher, historian of Philosophy, and inaugurator of the doxographic genre, anticipating the Peripatetic doxographical tradition, and setting him up as a kind of grey eminence behind Plato and Aristotle’s appreciation of the so-called “Presocratic Philosophy”. Although Mansfeld elaborated his contributions on Snell’s theory more carefully, even producing a major advance with identification of a Gorgian protodoxographical matrix parallel to the Hippian one, the lack of continuity in the protodoxographical studies (that remain practically frozen since 1986), resulted in a biased reception in which Mansfeld even started to function as a confirmer of Patzer’s excesses. Against this backdrop, this thesis intends to return to Snell and his successors in order to retrace the evolution of the protodoxographical theory, critically re-evaluate the evidence they produced, and add evidence that has been neglected, including recent studies on Hippias and other implicated characters. From this analysis, a more adequate profile for Hippias as an author, and a more adequate characterization of the structure and purpose of his Collection will emerge, as well as a more accurate characterization and consequent appreciation of the proto-doxographic contribution of Gorgias, and the identification of a possible new proto-doxographic source in the naturalistic physician Hippo.